Studies on deformation measurement with non-fixed camera using digital image correlation method. (1st January 2021) - Liang, Zhenning; Zhang, Jinxiu; Qiu, Longhui; Lin, Guangyi; Yin, Fengfu
Highlights: A digital image correlation technique with non-fixed camera is developed. The method is developed for deformation measurement in the field. The camera can move freely when capturing reference and target images. The technique is more flexible and convenient than traditional digital image correlation method. Abstract: A digital image correlation technique with non-fixed camera is developed for deformation measurement in the field since it is difficult to fix cameras when the deformations of a large number of areas need to be measured. Multiple reference and target images of the specimen surface and a feature template are captured from different orientations and corrected before the correlation calculation. The relative positions of the specimen surface and the camera are obtained by the camera calibration method. The specimen surface is divided to several meshes to reconstruct the speckle patterns. The technique is more flexible and convenient than traditional digital image correlation method in measuring the deformation of high altitude facilities such as bridges. In order to test the accuracy of this method, the deformations of an aluminum plate under different loading forces are measured and compared to the values recorded by the tensile tester.